Accurate Prediction of Gas Chromatographic Retention Times via Density Functional Theory Calculations: A Case Study Using Brominated Flame Retardants. Issue 8 (26th February 2020) - Izydorczak, Alexandra M.; Gross, Michael S.; Aga, Diana S.; Simpson, Scott
Abstract: Identification of structurally similar congeners of polybrominated diphenyl ether (PBDE) can be challenging without the use of analytical standards. Density Functional Theory (DFT) calculations paired with gas chromatographic (GC) retention times of reference standards were used to predict the retention times of PBDE congeners. This was accomplished by calculating polarizability of 31 PBDEs using the open‐sourced software package General Atomic and Molecular Electronic Structure System (GAMESS). Three PBDEs were randomly chosen from a training set of PBDEs and were treated as "unknowns" to test the accuracy of linear regressions constructed from calculated polarizabilities versus experimentally determined retention times. The top performing functionals predicted retention times of these "unknown" congeners to be within 1.3% and 3% for the DB‐5HT GC column and the ZB‐SemiVolatiles GC column, respectively. This study demonstrates that DFT calculations combined with experimental retention times can be used to aid in the identification of unknown analytes or, at the very least, reduce the number of plausible identities of analytes. Abstract : Density Functional Theory (DFT) calculations paired with gas chromatographic (GC) retention times of reference standards were used to predict the retention times of PBDE congeners. The top performing functionals predicted retention times of these "unknown" congeners were found to be within 1.3% and 3%. This study demonstrates that DFT calculations combined with experimental retention times can be used to aid in the identification of unknown analytes or reduce the number of plausible identities of analytes.